Tertiary lymphoid structures in autoimmune diseases - Dong, Yuanji; Wang, Ting; Wu, Huaxiang (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLSs) are organized lymphoid-like aggregations in non-lymphoid tissues. Tissues with chronic and persistent inflammation infiltration may drive and form ectopic germinal center-like structures, which are very common in autoimmune diseases, chronic infections, and tumor microenvironments. However, the mechanisms governing the formation of TLSs are still being explored. At present, it is not clear whether the formation of TLSs is associated with local uncontrolled immune inflammatory responses. While TLSs suggest a good prognosis in tumors, the opposite is true in autoimmune diseases. This review article will discuss the current views on initiating and maintaining TLSs and the potential therapeutic target in autoimmune diseases.